Pencegahan Kanker Serviks Melalui Edukasi Deteksi Dini Kanker Serviks di Poli Kintani RSUPN Cipto Mangunkusumo - Fajrin, Dessy; Sestu Iriami Mintaningtyas (Health Care : Journal of Community Service, 2024)
Abstract New cases of cervical cancer in 2018 were approximately 570,000, the fourth most common, and 6.6% of all cancers in women. About 90% of deaths from cervical cancer occur in low and middle income countries. The high mortality rate from cervical cancer globally can be reduced through a comprehensive approach that includes prevention, early diagnosis, effective screening and treatment programs. One of the causes of the high incidence of cervical cancer in Indonesia is the lack of early monitoring. The high incidence of cervical cancer in Indonesia is a health, economic and social burden for women everywhere. Partners in this activity are all patients who come to be examined at the Kintani RSCM polyclinic. Knowledge evaluation uses pre-test and post-test questionnaires. The assessment results show that the maximum minimum median score on the pretest is 7 (4-10) while the maximum minimum median score on the posttest is 8 (4-10). After carrying out the Wilcoxon test, p value = 0.002. The results of statistical tests show that there is an increase in knowledge before being given education on early detection of cervical cancer and after being given education on early detection of cervical cancer.